Analisis Pengaruh Inflasi dan Investasi Terhadap Pengangguran di Indonesia Periode Tahun 2012 - 2020 - Saidina Umar Nst; Irsad Lubis; Andra Monika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Inflation and unemployment are among the problems facing the national economy. Inflation means growth. Unemployment is defined as a condition in which a person in the labor force is unemployed and actively seeking work, or has been hired but has not yet started working. Broadly speaking, unemployment can be defined as a condition in which the supply of labor exceeds the demand for labor. The purpose of this study is to determine the impact of inflation and investment in Indonesia on unemployment. This study uses empirical techniques with a quantitative methodology, with population size representing the entire time series data on inflation, investment, and unemployment in Indonesia from 2012 to 2020. The data analysis technique used was multiple linear OLS regression. The results of this study conclude that inflation has no impact on unemployment, and investment has a positive impact on unemployment. This contradicts previous research by Fitrahwaty et al. (2004), which stated that inflation impacts unemployment, while investment has no effect at all. Based on previous research, the unemployment rate in Indonesia is influenced by the inflation rate and economic growth.